Interactive book: An Alternative tool for educating sexual abuse prevention in early childhood - Zahrina Mardhiyah; Aditya Nanda Priyatama (Jurnal Formil (Forum Ilmiah) Kesmas Respati, 2023)
In early childhood (0-6 years), lack of understanding of sexual organs, ease of manipulation along with the lower age of the child are strong risk factors for Child Sexual Abuse (CSA) in early childhood. Meanwhile, the eastern culture adopted in Indonesia tends to still regard the giving of its information as something taboo. Till now, there is no media for educating children about CSA prevention that can help parents in the process. So, this study aims to develop an interactive book as an educational tool for CSA prevention in early childhood so that adults, especially parents, feel more comfortable in providing understanding to children about CSA prevention. The method used is mixed methods on seven experts of psychology and early childhood education. Qualitative Descriptive Analysis was used to see the important improvement points in the development of interactive books. Meanwhile, quantitative analysis is used to see the feasibility of interactive books based on the expert's assessment which will be processed with Aiken’s v. The qualitative results show that the selection of themes, colors, words, illustrations, and sizes are important factors in the feasibility of books and improvement points in interactive books. Quantitatively, interactive books are considered worthy of being a tool for the prevention of CSA in early childhood with an Aiken’s v coefficient ranging from 0.75-0.93 for each sub-theme, which means worthy as a CSA prevention tool. The existence of an interactive self-protection book is expected to be a choice of educational media as well as an assessment for parents, teachers, or health workers in identifying cases of child sexual violence in their environment more comfortably without appearing rigid cause of taboo in eastern culture.